Salicylic acid remodeling of the rhizosphere microbiome induces watermelon root resistance against Fusarium oxysporum f. sp. niveum infection - Zhu, Feiying; Fang, Yong; Wang, Zhiwei; Wang, Pei; Yang, Kankan; Xiao, Langtao; Wang, Ruozhong (Frontiers in Microbiology, 2022)
Fusarium wilt disease poses a severe threat to watermelon cultivation, affecting the yield and quality of the fruit. We had previously found that the rhizosphere microbiome has a significant impact on the ability of watermelon plants to resist Fusarium wilt development and that salicylic acid (SA) is closely related to this phenomenon. Therefore, in this study, the role of SA as a mediator between plants and microbes in activating resistance against Fusarium oxysporum f. sp. niveum (FON) infection was explored through physiological, biochemical, and metagenomic sequencing experiments. As a result, we demonstrated that exogenous SA treatment could specifically increase some beneficial rhizosphere species that can confer resistance against FON inoculation, such as Rhodanobacter, Sphingomonas, and Micromonospora. Functional annotation analysis using common databases indicated that SA application significantly increased the relative abundance of glycoside hydrolase and polysaccharidelyase genes in the microbiome, which may have essential roles in increasing plant lipids. Moreover, network interaction analysis suggested that the AAC6_IIC gene highly expressed in species of phylum Proteobacteria may be manipulated through SA signal transduction pathways. In conclusion, these results provide a novel strategy for controlling Fusarium wilt of watermelon from the perspective of environmental ecology; that is, by manipulating the rhizosphere microbiome through phytohormones.